Molecular and morphological analyses to improve taxonomic classification of Metridia lucens/pacifica in the North Pacific. (28th April 2022) - Hirai, Junya; Chen, Fang; Itoh, Hiroshi; Tadokoro, Kazuaki; Lemay, Matthew A; Hunt, Brian P V; Tsuda, Atsushi
Abstract: Molecular and morphological analyses were used to resolve the taxonomy of Metridia lucens / pacifica in the North Pacific. Phylogenetic analysis of mitochondrial cytochrome c oxidase subunit I (mtCOI) revealed two lineages of M. lucens and M. pacifica with an average sequence difference of 13.0%, which were supported by variations in nuclear internal transcribed spacer sequences. Metridia pseudopacifica in the eastern Pacific, mentioned by Mackas and Galbraith (2002), was included in M. lucens . The presence of M. lucens and M. pacifica was confirmed across the North Pacific, and different genetic population structures were suggested between the two species in the North Pacific based on mtCOI sequences. The morphological identification character of length of setae on the fifth pair of legs was not useful for classifying adult female M. pacifica and M. lucens . There were regional variations in prosome length and head angle; these two characters successfully classified >98.2% of M. pacifica and M. lucens specimens from the North Pacific. As M. lucens and M. pacifica are key copepods in the North Pacific, accurate classification of individuals should be made in future studies to understand their relative contributions to marine ecosystems and improve detection of ecosystem change.